A systematic review and meta-analysis of loratadine combined with montelukast for the treatment of allergic rhinitis - Wang, Huan; Ji, Qing; Liao, Chao; Tian, Li (Frontiers in Pharmacology, 2023)
Background: Loratadine and montelukast are clinical first-line drugs in the treatment of allergic rhinitis (AR).However, there is no clear evidence of the efficacy of loratadine combined with montelukast in the treatment of AR. This study aimed to evaluate the efficacy and safety of the loratadine-montelukast combination on AR.In this meta-analysis, searches were conducted on PubMed, Embase, the Cochrane Central Register of Controlled Trials, Web of Science, and China National Knowledge Infrastructure (CNKI). The search terms included loratadine, montelukast, allergic rhinitis, and clinical trials. Meta-analyses were conducted using Rev Man 5.3 and Stata 15 statistical software.Results: A total of 23 studies with 4902 participants were enrolled. For the primary outcome, pooled resultsshowed that loratadine-montelukast can significantly reduce total nasal symptom scores (TNSS), when compared with loratadine (SMD, −1.00; 95% CI, −1.35 to −0.65, P < 0.00001), montelukast (SMD, −0.46; 95% CI, −0.68 to −0.25, P < 0.0001), or placebo (SMD, −0.93; 95% CI, −1.37 to −0.49, P < 0.00001). For secondary outcomes, pooled results showed that compared with loratadine, loratadine-montelukast can significantly improve nasal congestion, nasal itching, nasal sneezing, nasal rhinorrhea, and rhinoconjunctivitis quality of life questionnaires (RQLQ). Compared with montelukast, loratadine-montelukast can significantly improve nasal itching, and nasal sneezing. Compared with placebo, loratadine-montelukast can significantly improve nasal congestion, and RQLQ.Loratadine-montelukast combination is superior to loratadine monotherapy, montelukast monotherapy, or placebo in improving AR symptoms. Therefore, loratadine-montelukast combination can be an option for patients with moderate-severe AR or poorly response to monotherapy.Systematic review registration number: CRD42023397519.